ANALISIS KEBUTUHAN BAHASA INGGRIS PADA MAHASISWA NON BAHASA INGGRIS - Arin Arianti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the needs of English in non-English students according to the expected target vocational needs. Subjects in this research are students of Economics Faculty of semester 2 of Veteran Bangun Nusantara Sukoharjo University. The approach method is done by qualitative method. Methods of data collection by questionnaire, interview and documentation. Research target is to know the requirement of English for student of Faculty of Economics in terms of requirement (neccessities), desire and lacks so that can be categorized learn English to prepare for lecture (EAP) or for the purpose of facing work competition (EOP). Keywords: needs analysis, special English.